Ontologi dan Konsep Realitas dalam Kalam Al-Juwayni: Eksistensi, Tuhan, dan Makhluk - Hasna Zakiyah Amany (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study explores the ontological and metaphysical thought of Imam al-Juwayni, a prominent scholar in the Islamic kalām tradition, focusing on the concepts of existence, God, and created beings. The background of the study lies in the enduring relevance of classical Islamic philosophical and theological discussions on the nature of reality, divine attributes, and the relationship between God and creatures. The purpose of the study is to examine how al-Juwayni conceptualizes the distinction between the absolute existence of God and the contingent existence of creatures, as well as the implications of his thought for ethics, law, and human agency. The research employs a qualitative, descriptive method based on library research, analyzing primary texts of al-Juwayni and relevant secondary literature to uncover his philosophical arguments and theological reasoning. The findings reveal that al-Juwayni emphasizes the independence and necessity of God’s existence, while all created beings are contingent and dependent on divine will, yet retain limited agency. He integrates reason and revelation to understand divine attributes, creating a framework where metaphysics, ethics, and law are interconnected. The study concludes that al-Juwayni’s ontological perspective not only enriches classical Islamic thought but also provides a valuable conceptual foundation for contemporary discussions on theology, philosophy, and moral responsibility. His insights remain relevant for addressing modern social, ethical, and philosophical issues within an Islamic framework.